Identifying Patients at High Risk of Loss of Response to Infliximab Maintenance Therapy in Paediatric Crohn's Disease. (28th January 2016) - Dupont-Lucas, Claire; Sternszus, Robert; Ezri, Jessica; Leibovitch, Samantha; Gervais, France; Amre, Devendra; Deslandres, Colette
Abstract: Background and aims: Loss of response to infliximab resulting in discontinuation of therapy is a frequent problem encountered in paediatric Crohn's disease. Although identifying patients at risk of failure could have important implications for follow-up, literature in this area remains sparse. Our primary aim was to identify predictors of loss of response to infliximab among patients who were responders to induction. The secondary aim was to identify predictors of non-response to induction. Methods: A retrospective cohort of patients with paediatric Crohn's disease treated with infliximab between 2000 and 2013 was followed until loss of response to infliximab or transfer to adult care. Predictors of response to induction therapy were studied by multivariate logistic regression. Time to treatment failure was analysed with a multivariate Cox model. Results: Two-hundred and forty-eight patients were eligible for the study. Of these, 196 (79%) were responders to induction (57% clinical remission and 22% clinical response) and 52 (21%) were non-responders. Steroid resistance was the only variable independently associated with primary non-response (odds ratio [OR] 4.57, 95% confidence interval [CI] 1.67–12.50, p = 0.002). Thirty-one of the 196 responders discontinued infliximab due to loss of response after a mean of 1.6±1.3 years of treatment. Predictors of loss of response were level of response to induction (clinical response vs clinical remission, hazard ratio [HR] 3.74, 95% CI 1.80–7.80, p = 0.0004) and isolated colonic disease (HR 2.72, 95% CI 1.30–5.71, p = 0.008). Conclusions: Patients who fail to achieve clinical remission after induction and/or who have isolated colonic disease are at increased risk of loss of response to infliximab.